Mortality Risk Factors in Continuous Ambulatory Peritoneal Dialysis Patients - Widiaputro, Dandi; Gunawan, Atma; Rifai, Achmad (Universitas Brawijaya, 2026)
Background: Chronic Kidney Disease (CKD) is a common kidney disorder among elderly individuals and is a leading cause of global mortality. Patients undergoing Continuous Ambulatory Peritoneal Dialysis (CAPD) are at high risk of complications and mortality. Therefore, analyzing risk factors for mortality in CAPD patients is crucial. Aim: To identify mortality risk factors in CAPD patients. Methods: This study was an observational retrospective study design. The sample consisted of CAPD patients at Saiful Anwar Hospital in Malang, with data collection from August 1st, 2019 to July 31st, 2023. Information collected included demographic data, medical history, and laboratory parameters. Data were analyzed using chi-square tests, t-tests, Kolmogorov-Smirnov tests, and multiple logistic regression to evaluate relationships, normality, risk factor effects, and the mortality rate of CAPD patients. Results: There were 377 subjects who met the inclusion criteria, consist of deceased (n=89) and alive (n=288) subjects. Older age significantly increased mortality risk with an odds ratio (OR) of 1.277 (95% CI: 1.260-1.294; p = 0.007). Diabetes mellitus increased mortality risk in CAPD patients, with an OR of 3.185 (95% CI: 1.427-7.105; p = 0.005). Heart failure increased mortality risk in CAPD patients, with an OR of 4.201 (95% CI: 2.170-8.133; p = 0.000). Decreased potassium levels increased mortality risk in CAPD patients, with an OR of 1.352 (95% CI: 1.020-1.792; p = 0.036). Conclusion: Older age, diabetes mellitus, heart failure, and decreased potassium levels increase mortality risk in CAPD patients.